An Introduction to Kriya Yoga: A Philosophico-Literary Review - Kumari, Kanchan; Verma, Avichal (International Research Journal of Ayurveda & Yoga, 2025)
This literature review presents an overview of Kriya Yoga and its significance in traditional and modern contexts. The content for this review has been extracted from the Puranas, Upanishads, Bhagavad Gita, Tantric texts, Vedanta literature, and classical Kriya Yoga writings, as well as a total of 14 books and one relevant PubMed-indexed article identified using various keywords. Kriya Yoga is an ancient psycho-spiritual discipline aimed at accelerating human growth by synchronizing the body, mind, and consciousness. Deeply rooted in the yogic tradition, its philosophical foundations are found across the classical scriptures, and Maharshi Patanjali and Mahavatar Babaji later systematized it, and more recently propagated worldwide by Paramahansa Yogananda. The practice integrates specific pranayama techniques, meditation, and ethical living, designed to purify the nervous system, regulate life energy (Prana), and awaken higher states of consciousness. Current interdisciplinary studies suggest that Kriya Yoga influences psychophysiological parameters such as autonomic balance, neuroplasticity, and emotional regulation. These effects are further associated with measurable changes in brain regions. From a philosophical perspective, Kriya Yoga resonates with the non-dual vision of awareness, wherein the practitioner transcends egoic identification and realizes unity with the Self. Thus, Kriya Yoga represents not merely a set of techniques but a holistic path that combines spirituality, psychology, and subtle physiology, bridging ancient wisdom. The evidence indicates that Kriya Yoga, when practiced regularly with concentration, dedication, and patience, enhances both physical and mental well being. Moreover, it inspires practitioners to transcend the ego and move toward a state of expanded consciousness.